TI_GERICHTE 12.2011.167 vom 26. Juni 2013 , Gestione patrimoniale - responsabilità della banca - calcolo del danno - benchmark - TI Tribunale d'appello (2013)
Gestione patrimoniale - responsabilità della banca - calcolo del danno - benchmark